2021
DOI: 10.1002/chem.202004711
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Cucurbit[n]urils and Their Derivatives in the Capture of Hazardous Chemicals

Abstract: Cucurbit[n]urils (Q[n]s) are a relatively young family of macrocycles, consisting of glycoluril units bridged by methylene groups, and their unique structures have attracted extensive attention from chemists in recent decades. Due to the presence of a rigid hydrophobic inner cavity and two polar outer portals lined with carbonyl groups, Q[n]s not only encapsulate guest species into the cavity, but also coordinate with metal ions/clusters. Considerable achievements have been obtained in the fields of Q[n]s‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Cucurbit­[ n ]­urils (Q­[ n ]­s or CB­[ n ]­s, n = 5–8, 10, and 13–15) are classical macrocyclic hosts formed by acid-catalyzed condensation of glycoluril and formaldehyde (Figure ) with cavity size of 2.4–11.0 Å and a common depth (9.1 Å). Compared with other macrocycles, such as crown ethers, cryptands, cyclodextrins, calixarenes, and pillararenes, , Q­[ n ]­s distinguish themselves by their excellent ability to form inclusion complexes with various guest molecules, especially cationic guests, with high selectivity and high affinity in aqueous solution attributed to their rigid pumpkin-shaped structures and the corresponding macrocyclic-confinement effect. , Notably, early host–guest studies on cucurbiturils have already revealed that the Q­[ n ]-derived confined spaces generally result in profound changes of the physicochemical properties of the encapsulated dye guests such as absorption/emission wavelengths and quantum yields, which has been reviewed and discussed with other macrocycles by Nau and co-workers in 2011 . However, the size-dependent macrocyclic confinement , is commonly regarded as the hydrophobic effect in Q­[ n ]-based supramolecular luminescent assemblies in aqueous solution and has received little attention so far …”
Section: Introductionmentioning
confidence: 99%
“…Cucurbit­[ n ]­urils (Q­[ n ]­s or CB­[ n ]­s, n = 5–8, 10, and 13–15) are classical macrocyclic hosts formed by acid-catalyzed condensation of glycoluril and formaldehyde (Figure ) with cavity size of 2.4–11.0 Å and a common depth (9.1 Å). Compared with other macrocycles, such as crown ethers, cryptands, cyclodextrins, calixarenes, and pillararenes, , Q­[ n ]­s distinguish themselves by their excellent ability to form inclusion complexes with various guest molecules, especially cationic guests, with high selectivity and high affinity in aqueous solution attributed to their rigid pumpkin-shaped structures and the corresponding macrocyclic-confinement effect. , Notably, early host–guest studies on cucurbiturils have already revealed that the Q­[ n ]-derived confined spaces generally result in profound changes of the physicochemical properties of the encapsulated dye guests such as absorption/emission wavelengths and quantum yields, which has been reviewed and discussed with other macrocycles by Nau and co-workers in 2011 . However, the size-dependent macrocyclic confinement , is commonly regarded as the hydrophobic effect in Q­[ n ]-based supramolecular luminescent assemblies in aqueous solution and has received little attention so far …”
Section: Introductionmentioning
confidence: 99%
“…An important macrocycle that has so far only been used as a pollutant sorbent for dyes, metal cations, and oils on the monomeric rather than polymeric level is CB. 79,80 A substantial contribution to the field of CB-based COPs comes from the group of Kimoon Kim, who has extensively investigated the potential of template-free thiol-ene photopolymerization in the synthesis of CB-based COPs. 81 Although these materials were not used for environmental remediation, they were the first CB-based covalently self-assembled structures, and subsequent studies performed with them could easily be applied to pollutant capture.…”
Section: Other Macrocyclesmentioning
confidence: 99%
“…Among various macrocyclic compound cucurbit[n]uril (CB[n], n=5–8, 10, 13–15) hosts are promising macrocyclic molecules that contain a hydrophobic cavity enclosed by two polar carbonyl portals. Their uncommon binding nature make them superior host molecules and they play an important part in the design and constructions of novel host‐guest (H−G) SPM compounds for the progress of molecular device [11–16] . Contrary to a covalent bond, the noncovalent interactions among the host and the guest are often reversible and stimuli‐responsive, forming the basis of the design of dynamic H−G complexes with tunable properties.…”
Section: Introductionmentioning
confidence: 99%